Post-Harvest Grain Storing and Hedging with Efficient Futures - Terry L. Kastens; Kevin C. Dhuyvetter (Journal of Agricultural and Resource Economics, 1999)
This study simulates whether Kansas wheat, soybean, corn, and milo producers could have profitably used deferred futures plus historical basis cash price expectations for post-harvest unhedged and hedged grain storage decisions from 1985-97. The signaled storage decision is compared to a representative Kansas producer whose crop sales mimic average Kansas marketings each year. Using 23 grain price locations, the simulations resulted in an 11 cents per bushel annual increase in grain storage profits for wheat, 27 cents for soybeans, -17 cents for corn, and -20 cents for milo; however, storage profit differences varied substantially across locations. Hedging tended to decrease risk, but not impact profitability.